Rasgos esquileos en la caracterización de algunos personajes sofocleos - Bañuls Oller, José Vicente; Morenilla Talens, Carmen (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2008)
In contrast with ignorance as the source of the tragic error which characterizes the heroes of Sophocles, the heroes of Aeschylus are fully aware of their actions. However, the degree of their awareness is altered by a negative force which emerges from their lineage. These Aeschylean features are positively presented in Sophocles‚ Antigone.